A survey on graduation thesis writing of Vietnam’s university students majoring in Chinese teaching as a foreign language - Son, Nguyen Thi (Journal of Chinese Language and Culture Studies, 2023)
This study investigates the current situation of graduation thesis writing among undergraduates of Chinese Teaching as a Foreign language major in five universities in Vietnam from four aspects: the factors influencing whether students choose to write graduation thesis, the topic selection and form of graduation thesis, the difficulties in writing graduation thesis and the examination and evaluation process of graduation thesis. The study found that the lack of curriculum in Vietnamese universities resulted in the lack of essay writing skills and awareness of students. The number of students who choose to write graduation thesis every year is small, the quality of the thesis is low, and the degree of dependence on the Advisor is high. graduation thesis is mainly in the form of monographic research and investigation report, and there are few papers in the form of teaching experiment, teaching design and case analysis. The thesis topic is lack of innovation, and the major development trend is not updated in time. There is no effective way for students to find references, and the regulations and review process of graduation thesis are not rigorous enough. This study thinks that in order to improve these problems and improve the quality of students' graduation thesis, it should be reformed from top to bottom :(1) Adjust the curriculum and strengthen the training of thesis writing skills; (2) Appropriate attention should be paid to the graduation thesis, which is stipulated as a necessary condition for students to obtain the degree certificate, and the requirements of the thesis should be standardized; (3) Establish data database as soon as possible to provide convenience for students to find references and school papers.